APLIKASI SEARCH ENGINE DENGAN METODE DEPTH FIRST SEARCH (DFS) - Noni Juliasari; Joseph Christian Sitompul (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2012)
Along with the times and technology, it turns out that the demand for information is increased. The information required should also be obtained quickly and accurate. From a variety of technologies to obtain information, one of which is search engine. The role of technology search engine becomes increasingly important in information technology, especially in obtaining the up-to-date information. For example, sometimes we want to know what information is held by an area in the rest of the world, because maybe the area is an area of our prospects or a resource area. This study will discuss the development of simple search engine application by using depth first search method. It is hoped this this assessment will be useful and will be better in the future.Keywords: Search Engine, DFS, URL